FOOD WASTE IN BOARDING SCHOOLS: A SYSTEMATIC LITERATUR REVIEW - Andi Eka Yunianto; Sugirah Nour Rahman; Windi Indah Fajar Ningsih (JGK: Jurnal Gizi dan Kesehatan, 2026)
Six studies from South Africa, Indonesia, China, and Taiwan documented food waste in boarding schools and comparable educational settings. In an Islamic boarding school, one study measured a mean waste rate of 4.36% (SD 8.41%), while another in a similar setting found that food temperature issues significantly increased waste (p = 0.023). In university dining halls, plate waste ranged from 16.9% to 26.7%, reaching 555 g per student per day. In primary/middle schools, 130 g were wasted per meal (21% of food served), and in private high schools, waste rates ranged from 14.71% to 25.25%. Frequently discarded items included vegetables, desserts, staple foods, side dishes, and rice/noodles. Institutional practices, such as booking systems, menu design, and service logistics, along with behavioural factors, such as dietary habits and awareness, underlie the observed waste. Economic analyses indicate that a 10% reduction in waste could yield annual savings of $80,000 or offset costs estimated at 0.31 billion yuan. One study quantified environmental losses at 15,560 tonnes of waste, 554 km² of land, and 23.12 million m³ of water. Recommendations focus on educational and administrative strategies, improved operational management, and enhanced feedback systems, although none of the studies have tested these interventions under controlled conditions.